2022
DOI: 10.1111/inr.12767
|View full text |Cite
|
Sign up to set email alerts
|

Professional values and ethical sensitivities of student nurses during the COVID‐19 pandemic

Abstract: BackgroundProfessional values in nursing are the foundation of ethical practice affecting patient care quality.AimThe purpose of the present study was to evaluate the development of professional values and ethical sensitivities among new nurses during the COVID‐19 pandemic.MethodsA prospective observational study with a pre‐test and post‐test design was used. The sample constituted students (n = 302). The Nurses Professional Values Scale‐Revised and Modified Moral Sensitivity Questionnaire for Student Nurses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…More importance an individual ascribes to a value statement was reflected in a higher total score, with scores below 43, between 43 and 86, and above 86 classified as overall low, medium or moderate, and high importance of professional values, respectively [ 7 ]. Studies conducted in Nigeria, Iran, Israel, Spain, and Turkey demonstrated scale reliability of the scale with a range of Cronbach Alphas from α = 0.81 to α = 0.96 [ 1 , 3 , 7 , 9 , 13 ]. This was also confirmed in this study ( α = 0.941).…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More importance an individual ascribes to a value statement was reflected in a higher total score, with scores below 43, between 43 and 86, and above 86 classified as overall low, medium or moderate, and high importance of professional values, respectively [ 7 ]. Studies conducted in Nigeria, Iran, Israel, Spain, and Turkey demonstrated scale reliability of the scale with a range of Cronbach Alphas from α = 0.81 to α = 0.96 [ 1 , 3 , 7 , 9 , 13 ]. This was also confirmed in this study ( α = 0.941).…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Professional nursing values are the foundation of daily nursing care practice [ 1 ] and a corner stone in the selection and training of future nurses [ 2 , 3 ]. To ensure quality ethical nursing care [ 4 , 5 ], these values serve as a guideline for their professional behavior [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has established a connection between the development of positive professionalism in nursing students and their subsequent positive perception of the nursing profession upon entering the workforce (Fitzgerald & Clukey, 2022; Tang et al, 2022). Recent studies also indicate that the COVID‐19 pandemic has influenced nursing students' professional development as well as the leaning process (Ayaz‐Alkaya & Akca, 2022; Russo et al, 2023). Consequently, gaining insights into methods for cultivating professionalism among pre‐licensure nursing students holds significant importance.…”
Section: Introductionmentioning
confidence: 99%